Dampak Layanan Waktu Pengiriman terhadap Kepuasan Pelanggan pada Perusahaan Jasa Ekspedisi : Studi Kasus : Lion Parcel Sub Agen Tegal - Supono Syafiq; Farrell Pratama Nugraha; Saifullah Maulana Muqlis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of information technology and the increasing use of e-commerce is driving demand for fast and reliable delivery services. This research aims to analyze the impact of delivery time services on customer satisfaction at expedition service companies, with a case study of Lion Parcel Sub Agent Tegal. The research method used is a quantitative method with a survey approach by distributing questionnaires to Lion Parcel Tegal customers. Data were analyzed using validity, reliability, correlation and simple regression tests with the help of SPSS 25 software. The research results showed that there was a significant relationship between delivery speed and customer satisfaction level, with a correlation value of 0.911 and an influence of 83%. This indicates that the faster the delivery service, the higher the level of customer satisfaction. It is hoped that this study can be a reference for expedition service companies in improving the quality of their services to compete in the competitive logistics industry.